Additive Manufacturing of Li-Ion Batteries: A Comparative Study between Electrode Fabrication Processes - Schmitt, Wolfgang; Coleman, Jonathan; Nicolosi, Valeria (My University, 2023)
Additive manufacturing strategies are gaining more importance in the context of lithium-ion batteries. The rapid prototyping, reduced waste and complex 3D structures achievable are powerful and attractive tools that are out of the reach of current fabrication techniques. Additionally, thanks to the potential that these manufacturing techniques hold for the fabrication of micro-energy storage devices, they are gaining increasing attention in the literature. Here, some of the more common additive manufacturing techniques are compared to standard methodologies by systematically evaluating their electrochemical performance and correlating it with the physical changes induced by the printing process. By using LTO/CNT-based inks, it is observed that the inner arrangement of the conductive additive is significatively altered depending on the technique used and that this has an impact on the rate performance of the device. By using a model that links the capacity-rate data to the physical properties of the batteries, it is possible to find the limiting factor on the printed electrodes and correlate it with the material arrangement that each technique produces.
PUBLISHED
cited By 0
Keywords: Li-ion batteries; nanoscale; nanosheets